Preparation method of polylactic acid nanofiber filtering membrane as well as product and application of polylactic acid nanofiber filtering membrane

Through coaxial electrostatic spinning technology, polymalicate spinning solution with tetrapholtate titanate decentralized solution is combined to prepare a high -surface potential and high filtration efficiency polymal acid nano -fiber filter membrane. , Achieve efficient and sustainable air filtration effects.

CN119372836APending Publication Date: 2025-01-28SHENHUA SHENDONG COAL GRP +3
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411706905.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, the filtration performance of traditional filter materials is poor and cannot maintain a high surface potential and excellent filtration performance for a longer period of time.

Method used

通过将聚乳酸纺丝液与四方相钛酸钡分散液进行同轴静电纺丝,制备聚乳酸纳米纤维过滤膜。该方法利用四方相钛酸钡的高介电常数和优异的压电性,促进四方相钛酸钡均匀分散在纤维表面,产生协同效应。

Benefits of technology

制备的聚乳酸纳米纤维过滤膜具有较高的表面电位、较高的过滤效率和较低的空气阻力,能够在长时间作用下保持较高的表面电位,具备优异的过滤性能和良好的生物相容性和可降解性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372836A_ABST
    Figure CN119372836A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a polylactic acid nanofiber filter membrane and a product and application thereof, and the preparation method of the polylactic acid nanofiber filter membrane comprises the following steps: providing a tetragonal phase barium titanate dispersion liquid and a polylactic acid spinning solution, and carrying out coaxial electrostatic spinning on the polylactic acid spinning solution and the tetragonal phase barium titanate dispersion liquid, and drying to obtain the polylactic acid nanofiber filter membrane. Wherein the mass ratio of tetragonal-phase barium titanate in the tetragonal-phase barium titanate dispersion liquid to polylactic acid in the polylactic acid spinning solution is 1: (1-10). According to the preparation method, the dosage of a polylactic acid spinning solution and a tetragonal-phase barium titanate dispersion solution is independently controlled through coaxial electrostatic spinning, and tetragonal-phase barium titanate is promoted to be uniformly dispersed on the surface of the fiber, so that the tetragonal-phase barium titanate and polylactic acid generate a synergistic effect; therefore, the polylactic acid nanofiber filter membrane with high surface potential, high filter efficiency and low air resistance is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of filter materials, and in particular to a preparation method of a polylactic acid nanofiber filter membrane, a product thereof and an application thereof. Background Art

[0002] In recent years, air pollution has caused considerable harm to human health. Therefore, daily wearing of masks is considered an effective way to protect oneself from particulate pollution. Currently, the filter materials used for personal protection on the market are mainly melt-blown electrostatic electret nonwoven materials and electrostatically spun nanofiber nonwoven materials. In this process, the polymer solution or melt undergoes extrusion and is quickly stacked by heat flow or high-voltage electrostatic field to produce nano- or micron-scale ultrafine fibers. Among them, the electret is a dielectric with a long-lasting charge that can store space charge and dipole charge for a long time, relying on the electrostatic effect to intercept tiny particles. However, traditional filter materials (such as polyester nonwovens, polypropylene meltblown cloth, glass fiber, etc.) have low filtration efficiency, and due to the inevitable electrostatic decay effect, they cannot maintain a high surface potential and excellent filtration performance for a long time.

[0003] In view of this, this application is hereby filed. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for preparing a polylactic acid nanofiber filter membrane and its product and application, so as to solve the problem that traditional filter materials in the prior art have poor filtering performance and cannot maintain a high surface potential and excellent filtering performance for a long time.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a polylactic acid nanofiber filtration membrane is provided, comprising the following steps: providing a tetragonal barium titanate dispersion and a polylactic acid spinning solution, coaxially electrospinning the polylactic acid spinning solution and the tetragonal barium titanate dispersion, and obtaining the polylactic acid nanofiber filtration membrane after drying; wherein the mass ratio of the tetragonal barium titanate in the tetragonal barium titanate dispersion to the polylactic acid in the polylactic acid spinning solution is 1:(1-10).

[0006] Furthermore, the mass concentration of tetragonal barium titanate in the tetragonal barium titanate dispersion is 10-30 wt %.

[0007] Furthermore, the mass concentration of polylactic acid in the polylactic acid spinning solution is 5 to 25 wt %.

[0008] Furthermore, the operating parameters of coaxial electrospinning are: the spinning voltage of the tetragonal barium titanate dispersion is 20-50 kV, and the consumption rate of the tetragonal barium titanate dispersion is 0.1-50 mL / h; the spinning voltage of the polylactic acid spinning solution is 20-50 kV, and the consumption rate of the polylactic acid spinning solution is 0.1-50 mL / h; the temperature is 10-30°C, the receiving distance is 10-30 cm, and the drum speed is 100-4000 rpm.

[0009] Furthermore, the solvent of the tetragonal barium titanate dispersion is a first organic solvent, and the first organic solvent includes at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform.

[0010] Furthermore, the tetragonal barium titanate dispersion also includes a dispersant.

[0011] Furthermore, the mass ratio of the dispersant to the tetragonal barium titanate is 1:100 to 1:1000.

[0012] Furthermore, the dispersant includes at least one of alkyl glycoside, polyvinyl pyrrolidone, ammonium polymethacrylate, sodium hexametaphosphate, dodecyldimethylaminoethyl lactone, and hexadecyltrimethylammonium bromide.

[0013] Furthermore, the solvent of the polylactic acid spinning solution is a second organic solvent; the second organic solvent includes at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform.

[0014] Furthermore, the preparation method of tetragonal barium titanate in the tetragonal barium titanate dispersion includes the following steps: mixing a barium source, an acid solution, a titanium source and an alcohol to obtain a barium titanate gel; and then calcining the barium titanate gel to obtain a tetragonal barium titanate.

[0015] Furthermore, the mass ratio of the barium source to the acid solution is (0.1-10):(99.9-90).

[0016] Furthermore, the mass ratio of the titanium source to the alcohol is (0.1-10):(99.9-90).

[0017] Furthermore, the molar ratio of the barium element in the barium source to the titanium element in the titanium source is 1:10 to 10:1.

[0018] Furthermore, the barium source includes at least one of barium sulfate, barium nitrate, barium acetate, barium hydroxide, barium chloride, and barium carbonate.

[0019] Furthermore, the acid solution includes at least one of acetic acid, hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.

[0020] Furthermore, the titanium source includes at least one of tetrabutyl titanate, isopropyl titanate, and tetraethyl titanate.

[0021] Furthermore, the alcohol includes at least one of methanol, ethanol, n-propanol, isopropanol, and isobutanol.

[0022] Furthermore, the calcination temperature is 500-1200° C., and the calcination time is 0.5-6 hours.

[0023] According to another aspect of the present invention, there is provided a polylactic acid nanofiber filtration membrane obtained by the preparation method provided in the first aspect above.

[0024] According to a third aspect of the present invention, there is provided a use of the polylactic acid nanofiber filter membrane provided in the second aspect in an air filter material.

[0025] The technical solution of the present invention is applied. The present application performs coaxial electrostatic spinning of polylactic acid spinning solution and tetragonal barium titanate dispersion, that is, in the process of electrostatic spinning of polylactic acid static spinning solution to obtain polylactic acid fiber, the tetragonal barium titanate dispersion is electrostatically sprayed onto the surface of polylactic acid fiber. The preparation method utilizes the high dielectric constant and excellent piezoelectricity of tetragonal barium titanate (BTO), independently controls the amount of polylactic acid spinning solution and tetragonal barium titanate dispersion by coaxial electrostatic spinning, and promotes the uniform dispersion of tetragonal barium titanate on the fiber surface, so that the tetragonal barium titanate and polylactic acid produce a synergistic effect, thereby preparing a polylactic acid nanofiber filter membrane with high surface potential, high filtration efficiency and low air resistance.

[0026] In addition, the polylactic acid nanofiber filter membrane can maintain a high surface potential even under long-term action, not only has excellent filtering performance, but also can generate piezoelectric charge through normal human breathing or wind vibration. In addition, it also has good biocompatibility and degradability, can achieve sustainable development of the environment, and is an air filtration material with broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0028] Figure 1 A SEM scanning electron microscope schematic diagram of tetragonal barium titanate in Example 2 is shown. DETAILED DESCRIPTION

[0029] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0030] As analyzed in the background technology of this application, the filtration performance of traditional filtration materials in the prior art is poor, and it is impossible to maintain a high surface potential and excellent filtration performance for a long time. In order to solve the above problems, this application provides a preparation method of a polylactic acid nanofiber filtration membrane and its product and application.

[0031] In a first typical embodiment of the present application, a method for preparing a polylactic acid nanofiber filter membrane is provided, the preparation method comprising the following steps: providing a tetragonal barium titanate dispersion and a polylactic acid spinning solution, coaxially electrospinning the polylactic acid spinning solution and the tetragonal barium titanate dispersion, and obtaining a polylactic acid nanofiber filter membrane after drying; wherein the mass ratio of the tetragonal barium titanate in the tetragonal barium titanate dispersion to the polylactic acid in the polylactic acid spinning solution is 1:(1 to 10).

[0032] Polylactic acid (PLA) is a bio-based, fully degradable, environmentally friendly polymer with excellent biocompatibility and easy processing. It is composed of chiral molecular chains and does not require polarization treatment with an external electric field. It can exhibit certain piezoelectricity through simple mechanical action. However, its piezoelectricity is usually low and cannot meet the requirements of generating piezoelectric charges through mechanical vibrations of breathing during air filtration to achieve the effects of electrostatic adsorption and long-term filtration. Tetragonal barium titanate (BTO) is a ferroelectric ceramic material with a high dielectric constant, excellent ferroelectricity, piezoelectricity and optical properties. It is one of the most researched functional materials.

[0033] The present application is to electrospin polylactic acid spinning solution and tetragonal barium titanate dispersion solution coaxially, that is, in the process of electrospinning the polylactic acid static spinning solution to obtain polylactic acid fiber, the tetragonal barium titanate dispersion solution is electrostatically sprayed onto the surface of the polylactic acid fiber. The preparation method utilizes the high dielectric constant and excellent piezoelectricity of tetragonal barium titanate (BTO), independently controls the amount of polylactic acid spinning solution and tetragonal barium titanate dispersion solution through coaxial electrospinning, and promotes the uniform dispersion of tetragonal barium titanate on the fiber surface, so that the tetragonal barium titanate and polylactic acid produce a synergistic effect, thereby preparing a polylactic acid nanofiber filter membrane with high surface potential, high filtration efficiency and low air resistance.

[0034] In addition, the polylactic acid nanofiber filter membrane can maintain a high surface potential even under long-term action, not only has excellent filtering performance, but also can generate piezoelectric charge through normal human breathing or wind vibration. In addition, it also has good biocompatibility and degradability, can achieve sustainable development of the environment, and is an air filtration material with broad application prospects.

[0035] Typically but not limitatively, the mass ratio of tetragonal barium titanate in the tetragonal barium titanate dispersion to polylactic acid in the polylactic acid spinning solution in the present application is 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or a range consisting of any two values.

[0036] In some embodiments, the drying temperature is 15-40° C., the relative humidity of the environment is 20-50%, and the drying time is 3-12 hours to obtain a polylactic acid nanofiber filtration membrane with better performance.

[0037] In order to further promote the stability of tetragonal barium titanate in the tetragonal barium titanate dispersion, the mass concentration of tetragonal barium titanate in the tetragonal barium titanate dispersion is preferably 10 to 30 wt %.

[0038] Typically but not limitatively, the mass concentration of tetragonal barium titanate in the tetragonal barium titanate dispersion provided in the present application is 10wt%, 15wt%, 20wt%, 25wt%, 30wt% or a range consisting of any two values.

[0039] In order to further promote the dissolution and stability of polylactic acid in the polylactic acid spinning solution, the mass concentration of polylactic acid in the polylactic acid spinning solution is preferably 5 to 25 wt %.

[0040] Typically but not limitatively, the mass concentration of polylactic acid in the polylactic acid spinning solution provided in the present application is 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or a range consisting of any two values.

[0041] In order to further improve the surface potential and filtration efficiency of the polylactic acid nanofiber filtration membrane, the operating parameters of the coaxial electrospinning are as follows: the spinning voltage of the tetragonal barium titanate dispersion is 20-50 kV, and the consumption rate of the tetragonal barium titanate dispersion is 0.1-50 mL / h; the spinning voltage of the polylactic acid spinning solution is 20-50 kV, and the consumption rate of the polylactic acid spinning solution is 0.1-50 mL / h; the temperature is 10-30 ° C, the receiving distance is 10-30 cm, and the drum speed is 100-4000 rpm.

[0042] Typically but not restrictively, the spinning voltage of the tetragonal barium titanate dispersion in the present application is 20kV, 25kV, 30kV, 35kV, 40kV, 45kV, 50kV or a range consisting of any two values; the consumption rate of the tetragonal barium titanate dispersion is 0.1mL / h, 0.5mL / h, 1mL / h, 5mL / h, 10mL / h, 20mL / h, 30mL / h, 40mL / h, 50mL / h or a range consisting of any two values; the spinning voltage of the polylactic acid spinning solution is 20kV, 25kV, 30kV, 35kV, 40kV, 45kV, 50kV or a range consisting of any two values; The consumption rate of the acid spinning solution is 0.1mL / h, 0.5mL / h, 1mL / h, 5mL / h, 10mL / h, 20mL / h, 30mL / h, 40mL / h, 50mL / h or a range consisting of any two values; the temperature is 10°C, 15°C, 20°C, 25°C, 30°C or a range consisting of any two values; the receiving distance is 10cm, 15cm, 20cm, 25cm, 30cm or a range consisting of any two values; the drum speed is 100rpm, 500rpm, 1000rpm, 2000rpm, 3000rpm, 4000rpm or a range consisting of any two values.

[0043] In some embodiments, the solvent of the tetragonal barium titanate dispersion is a first organic solvent. In order to further promote the dissolution of tetragonal barium titanate, the first organic solvent preferably includes any one or more of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform.

[0044] In order to further promote the dispersion of tetragonal barium titanate, it is preferred that the tetragonal barium titanate dispersion also includes a dispersant, and it is further preferred that the mass ratio of the dispersant to the tetragonal barium titanate is 1:100 to 1:1000; it is further preferred that the dispersant includes any one or more of alkyl glycoside, polyvinyl pyrrolidone, ammonium polymethacrylate, sodium hexametaphosphate, dodecyldimethylaminoethyl lactone, and hexadecyltrimethylammonium bromide.

[0045] Typically but not limitatively, the mass ratio of the dispersant to the tetragonal barium titanate in the tetragonal barium titanate dispersion provided in the present application is, for example, 1:100, 1:200, 1:400, 1:600, 1:800, 1:1000 or a range consisting of any two values.

[0046] In some embodiments, the solvent of the polylactic acid spinning solution is a second organic solvent. To further promote the dissolution and dispersion of polylactic acid, the second organic solvent preferably includes any one or more of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform.

[0047] The tetragonal barium titanate provided in the present application can be purchased from the market or prepared by oneself.

[0048] In some embodiments, the preparation method of tetragonal barium titanate includes the following steps: preparing tetragonal barium titanate by a sol-gel method, mixing a barium source, an acid solution, a titanium source and an alcohol to obtain a barium titanate gel; and then calcining the barium titanate gel to obtain a tetragonal barium titanate.

[0049] In order to further promote the formation of tetragonal barium titanate and further increase the content of tetragonal phase structure, the mass ratio of the barium source and the acid solution is preferably (0.1-10): (99.9-90), and the mass ratio of the titanium source and the alcohol is preferably (0.1-10): (99.9-90); the molar ratio of the barium element in the barium source to the titanium element in the titanium source is preferably 1:10-10:1.

[0050] Typically but not limiting, the mass of the barium source and the acid solution is, for example, 0.1:99.9, 0.5:99.5, 1:99, 3:97, 5:95, 8:92, 10:90 or a range consisting of any two values; the mass of the titanium source and the alcohol is, for example, 0.1:99.9, 0.5:99.5, 1:99, 3:97, 5:95, 8:92, 10:90 or a range consisting of any two values; the molar ratio of the barium element in the barium source to the titanium element in the titanium source is 1:10, 5:10, 1:1, 2:1, 5:1, 10:1 or a range consisting of any two values.

[0051] In order to further improve the purity and dispersibility of tetragonal barium titanate, the barium source preferably includes any one or more of barium sulfate, barium nitrate, barium acetate, barium hydroxide, barium chloride, and barium carbonate.

[0052] In order to further improve the purity and dispersibility of tetragonal barium titanate, the acid solution preferably includes any one or more of acetic acid, hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.

[0053] In order to further improve the purity and dispersibility of tetragonal barium titanate, the titanium source preferably includes any one or more of tetrabutyl titanate, isopropyl titanate, and tetraethyl titanate.

[0054] In order to further improve the purity and dispersibility of tetragonal barium titanate, the alcohol preferably includes any one or more of methanol, ethanol, n-propanol, isopropanol, and isobutanol.

[0055] In order to further improve the purity and dispersibility of tetragonal barium titanate, the calcination temperature is preferably 500 to 1200° C. and the calcination time is 0.5 to 6 hours.

[0056] Typically but not limiting, the calcination temperature is 500°C, 600°C, 800°C, 1000°C, 1200°C or a range consisting of any two values, and the calcination time is 0.5h, 1h, 2h, 4h, 6h or a range consisting of any two values.

[0057] In a second typical embodiment of the present application, a polylactic acid nanofiber filtration membrane obtained by the preparation method provided in the first typical embodiment is provided.

[0058] In a third typical embodiment of the present application, there is provided an application of the polylactic acid nanofiber filter membrane provided in the second typical embodiment in an air filter material.

[0059] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.

[0060] Example 1

[0061] This embodiment provides a method for preparing a polylactic acid nanofiber filter membrane, comprising the following steps:

[0062] Step S1, dissolving barium sulfate in acetic acid (the mass ratio of barium sulfate to acetic acid is 0.1:99.9), adding a mixed solution of tetrabutyl titanate and methanol (the mass ratio of tetrabutyl titanate to methanol is 5:95), stirring, adding 10 mL of deionized water, and obtaining barium titanate gel. The molar ratio of the barium element in the barium sulfate to the titanium element in the tetrabutyl titanate is 1:10. The barium titanate gel is calcined at 500°C for 6 hours to obtain tetragonal barium titanate;

[0063] Step S2, dispersing tetragonal barium titanate in chloroform, adding ammonium polymethacrylate (the mass ratio of ammonium polymethacrylate to tetragonal barium titanate is 1:1000), and ultrasonically oscillating to obtain a tetragonal barium titanate dispersion, wherein the mass concentration of the tetragonal barium titanate is 10wt%;

[0064] Step S3, dissolving polylactic acid in a mixed solution of chloroform and ethanol (the mass ratio of chloroform to ethanol is 7:3) to form a polylactic acid spinning solution, wherein the mass concentration of the polylactic acid is 20wt%;

[0065] Step S4, the above-mentioned tetragonal barium titanate dispersion and polylactic acid spinning solution are placed in two electrospinning syringes (tetragonal barium titanate dispersion is placed in the shell layer, and polylactic acid spinning solution is placed in the core layer), and coaxial electrospinning is performed, and the operating parameters are: the spinning voltage of the tetragonal barium titanate dispersion is 20kV, and the syringe propulsion rate of the tetragonal barium titanate dispersion is 0.1mL / h; the spinning voltage of the polylactic acid spinning solution is 20kV, and the syringe propulsion rate of the polylactic acid spinning solution is 0.1mL / h; the temperature is 25°C, the receiving distance between the drum and the needle is 10cm, the drum speed is 100rpm, and the temperature is 15°C and the relative humidity is 20% for 12 hours to obtain a polylactic acid nanofiber filter membrane. The mass ratio of tetragonal barium titanate and polylactic acid in the polylactic acid nanofiber filter membrane is 1:2, and the thickness of the polylactic acid nanofiber filter membrane is 50μm.

[0066] Example 2

[0067] This embodiment provides a method for preparing a polylactic acid nanofiber filter membrane, comprising the following steps:

[0068] Step S1, dissolve barium acetate in hydrochloric acid (the mass ratio of barium acetate to hydrochloric acid is 10:90), add a mixed solution of isopropyl titanate and ethanol (the mass ratio of isopropyl titanate to ethanol is 0.1:99.9), stir, add 8 mL of deionized water, and obtain barium titanate gel. Among them, the molar ratio of the barium element in barium acetate to the titanium element in isopropyl titanate is 10:1. The barium titanate gel is calcined at 1200°C for 0.5h to obtain tetragonal barium titanate. The SEM scanning electron microscope image of the tetragonal barium titanate is as follows Figure 1 As shown (tested at 20 kV using a field emission scanning electron microscope (SU8229, Hitachi, Japan));

[0069] Step S2, dispersing tetragonal barium titanate in dichloromethane, adding hexadecyltrimethylammonium bromide (the mass ratio of hexadecyltrimethylammonium bromide to tetragonal barium titanate is 1:100), and ultrasonically oscillating to obtain a tetragonal barium titanate dispersion, wherein the mass concentration of the tetragonal barium titanate is 25wt%;

[0070] Step S3, dissolving polylactic acid in a mixed solution of dichloromethane and acetone (the mass ratio of dichloromethane to acetone is 6:4) to form a polylactic acid spinning solution, wherein the mass concentration of the polylactic acid is 25wt%;

[0071] Step S4, the above-mentioned tetragonal barium titanate dispersion and polylactic acid spinning solution are placed in two electrostatic spinning syringes (tetragonal barium titanate dispersion is placed in the shell layer, and polylactic acid spinning solution is placed in the core layer), and coaxial electrostatic spinning is performed, and the operating parameters are: the spinning voltage of the tetragonal barium titanate dispersion is 50kV, and the syringe propulsion rate of the tetragonal barium titanate dispersion is 10mL / h; the spinning voltage of the polylactic acid spinning solution is 50kV, and the syringe propulsion rate of the polylactic acid spinning solution is 50mL / h; the temperature is 30°C, the receiving distance between the drum and the needle is 30cm, the drum speed is 1000rpm, and the temperature is 40°C and the relative humidity is 50% for 3h to obtain a polylactic acid nanofiber filter membrane. The mass ratio of tetragonal barium titanate and polylactic acid in the polylactic acid nanofiber filter membrane is 1:5, and the thickness of the polylactic acid nanofiber filter membrane is 5μm.

[0072] Example 3

[0073] This embodiment provides a method for preparing a polylactic acid nanofiber filter membrane, comprising the following steps:

[0074] Step S1, dissolve barium nitrate in nitric acid (the mass ratio of barium nitrate to nitric acid is 0.5:99.5), add a mixed solution of tetraethyl titanate and isopropanol (the mass ratio of tetraethyl titanate to isopropanol is 2:98), stir, add 9 mL of deionized water, and obtain barium titanate gel. Among them, the molar ratio of the barium element in the barium nitrate to the titanium element in the tetraethyl titanate is 1:1. The barium titanate gel is calcined at 1000°C for 2 hours to obtain tetragonal barium titanate;

[0075] Step S2, dispersing tetragonal barium titanate in dimethylformamide and ethanol (the mass ratio of dimethylformamide to ethanol is 1:1), adding sodium hexametaphosphate (the mass ratio of sodium hexametaphosphate to tetragonal barium titanate is 1:100), and ultrasonically oscillating to obtain a tetragonal barium titanate dispersion, wherein the mass concentration of the tetragonal barium titanate is 30wt%;

[0076] Step S3, dissolving polylactic acid in a mixed solution of ethyl acetate and ethanol (the mass ratio of ethyl acetate to ethanol is 5:5) to form a polylactic acid spinning solution, wherein the mass concentration of the polylactic acid is 10wt%;

[0077] Step S4, placing the tetragonal barium titanate dispersion and the polylactic acid spinning solution in two electrospinning syringes respectively (the tetragonal barium titanate dispersion is placed in the shell layer, and the polylactic acid spinning solution is placed in the core layer), and coaxial electrospinning is performed, and the operating parameters are: the spinning voltage of the tetragonal barium titanate dispersion is 30kV, and the syringe propulsion rate of the tetragonal barium titanate dispersion is 1mL / h; the spinning voltage of the polylactic acid spinning solution is 25kV, and the syringe propulsion rate of the polylactic acid spinning solution is 24mL / h; the temperature is 25°C, the receiving distance between the drum and the needle is 20cm, the drum speed is 300rpm, and the polylactic acid nanofiber filter membrane is dried at a temperature of 30°C and a relative humidity of 40% for 6h to obtain the polylactic acid nanofiber filter membrane, the mass ratio of tetragonal barium titanate and polylactic acid in the polylactic acid nanofiber filter membrane is 1:8, and the thickness of the polylactic acid nanofiber filter membrane is 31μm.

[0078] Example 4

[0079] This embodiment provides a method for preparing a polylactic acid nanofiber filter membrane, comprising the following steps:

[0080] Step S1, dissolve barium carbonate in sulfuric acid (the mass ratio of barium carbonate to sulfuric acid is 1:99), add a mixed solution of tetrabutyl titanate and n-propanol (the mass ratio of tetrabutyl titanate to n-propanol is 2.5:97.5), stir, add 10mL of deionized water, and obtain barium titanate gel. Among them, the molar ratio of the barium element in the barium carbonate to the titanium element in the tetrabutyl titanate is 1:2. The barium titanate gel is calcined at 900°C for 3h to obtain tetragonal barium titanate;

[0081] Step S2, dispersing tetragonal barium titanate in dichloromethane, adding dodecyl dimethylamine ethyl lactone (the mass ratio of dodecyl dimethylamine ethyl lactone to tetragonal barium titanate is 1:200), and ultrasonically oscillating to obtain a tetragonal barium titanate dispersion, wherein the mass concentration of the tetragonal barium titanate is 10wt%;

[0082] Step S3, dissolving polylactic acid in chloroform to form a polylactic acid spinning solution, wherein the mass concentration of the polylactic acid is 5wt%;

[0083] Step S4, placing the tetragonal barium titanate dispersion and the polylactic acid spinning solution in two electrospinning syringes respectively (the tetragonal barium titanate dispersion is placed in the shell layer, and the polylactic acid spinning solution is placed in the core layer), and coaxial electrospinning is performed, and the operating parameters are: the spinning voltage of the tetragonal barium titanate dispersion is 40kV, and the syringe propulsion rate of the tetragonal barium titanate dispersion is 2.5mL / h; the spinning voltage of the polylactic acid spinning solution is 35kV, and the syringe propulsion rate of the polylactic acid spinning solution is 5mL / h; the temperature is 27°C, the receiving distance between the drum and the needle is 20cm, the drum speed is 400rpm, and the temperature is 35°C and the relative humidity is 42% for 6h to obtain a polylactic acid nanofiber filter membrane, in which the mass ratio of tetragonal barium titanate and polylactic acid in the polylactic acid nanofiber filter membrane is 1:1, and the thickness of the polylactic acid nanofiber filter membrane is 24μm.

[0084] Example 5

[0085] The difference from Example 3 is that in Example 5, by controlling the syringe advancement rate, the mass ratio of tetragonal barium titanate and polylactic acid in the polylactic acid nanofiber filter membrane is 1:10, and the thickness of the obtained polylactic acid nanofiber filter membrane is 31 μm.

[0086] Example 6

[0087] The difference from Example 3 is that Example 6 adjusts the amount of tetragonal barium titanate in the tetragonal barium titanate dispersion so that the mass concentration of the tetragonal barium titanate is 2wt%, and adjusts the syringe propulsion rate of the tetragonal barium titanate dispersion to 15mL / h. The mass ratio of tetragonal barium titanate to polylactic acid in the obtained polylactic acid nanofiber filter membrane is 1:8, and the thickness of the polylactic acid nanofiber filter membrane is 53μm.

[0088] Example 7

[0089] The difference from Example 3 is that Example 7 adjusts the amount of tetragonal barium titanate in the tetragonal barium titanate dispersion so that the mass concentration of tetragonal barium titanate is 50wt%. The mass ratio of tetragonal barium titanate to polylactic acid in the obtained polylactic acid nanofiber filter membrane is 1:4.8, and the thickness of the polylactic acid nanofiber filter membrane is 56μm.

[0090] Comparative Example 1

[0091] The difference from Example 1 is that in Comparative Example 1, the polylactic acid spinning solution is placed in an electrospinning syringe, and the electrospinning conditions are: voltage of 20 kV, syringe propulsion rate of 0.1 mL / h, roller receiving distance of 10 cm, and roller speed of 100 rpm to obtain a nanofiber membrane. The nanofiber membrane is immersed in a tetragonal barium titanate dispersion for 30 min, and after the immersion is completed, it is placed in a 40° C. oven for drying for 12 h to obtain a polylactic acid nanofiber filter membrane, the thickness of the polylactic acid nanofiber filter membrane is 37 μm, and the content of tetragonal barium titanate in the polylactic acid nanofiber filter membrane is 0.02 wt%.

[0092] Comparative Example 2

[0093] The difference from Example 2 is that, in Comparative Example 2, polylactic acid is dissolved in a mixed solution of dichloromethane and acetone (the mass ratio of dichloromethane to acetone is 6:4), and then tetragonal barium titanate is added, and ultrasonic dispersion is performed for 1h to obtain an electrospinning mixture. The electrospinning mixture is subjected to electrospinning, and the operating parameters are: spinning voltage is 50kV, syringe propulsion rate is 50mL / h, drum receiving distance is 30cm, and drum speed is 1000rpm to obtain a polylactic acid nanofiber filter membrane, the thickness of the polylactic acid nanofiber filter membrane is 7μm, and the content of tetragonal barium titanate in the polylactic acid nanofiber filter membrane is 10wt%.

[0094] Comparative Example 3

[0095] The difference from Example 3 is that no tetragonal barium titanate is added in the preparation process of Comparative Example 3. The specific steps are: dissolving polylactic acid in a mixed solution of ethyl acetate and ethanol (the mass ratio of ethyl acetate to ethanol is 5:5) to form a polylactic acid spinning solution, wherein the mass concentration of polylactic acid is 10wt%. The polylactic acid spinning solution is electrospun, and the operating parameters are: the spinning voltage of the polylactic acid spinning solution is 25kV, the syringe propulsion rate of the polylactic acid spinning solution is 0.8mL / h; the temperature is 23°C, the receiving distance between the drum and the needle is 20cm, and the drum speed is 300rpm, to obtain a polylactic acid nanofiber filter membrane, the thickness of the polylactic acid nanofiber filter membrane is 27μm.

[0096] Comparative Example 4

[0097] The difference from Example 3 is that in Comparative Example 4, by controlling the syringe pushing rate, the mass ratio of tetragonal barium titanate and polylactic acid in the polylactic acid nanofiber filter membrane is 1:20, and the thickness of the obtained polylactic acid nanofiber filter membrane is 41 μm.

[0098] Comparative Example 5

[0099] The difference from Example 3 is that in Comparative Example 5, by controlling the syringe propulsion rate, the mass ratio of tetragonal barium titanate and polylactic acid in the polylactic acid nanofiber filter membrane is 1:0.05, and the thickness of the obtained polylactic acid nanofiber filter membrane is 34 μm.

[0100] Comparative Example 6

[0101] The difference from Example 3 is that in Comparative Example 6, the crystal phase of barium titanate is adjusted to make it cubic barium titanate (cubic barium titanate is purchased from Sinopharm Chemical Reagent Co., Ltd.), and the thickness of the polylactic acid nanofiber filtration membrane is 40 μm.

[0102] Test Example 1

[0103] The polylactic acid nanofiber filtration membrane samples provided in the above embodiments and comparative examples were subjected to dielectric constant test, piezoelectric constant test, surface potential test, filtration performance test, and air resistance test. The results are shown in Table 1.

[0104] Dielectric constant test: The polylactic acid nanofiber filter membrane samples were cut into discs with a diameter of 1 cm, and the dielectric constant was tested using a dielectric constant tester (WK-6500B, Wayne Kerr Electronics Ltd., UK) according to the international standard ASTM D150 method.

[0105] Piezoelectric constant test: The polylactic acid nanofiber filter membrane sample was subjected to d33 test using a d33 pressure gauge system (PM300 model) with a frequency of 110 Hz, a dynamometer setting of 1.0 N, and a dynamic force setting of 0.25 N.

[0106] Surface potential test: A non-contact electrostatic meter (VM54XQS, Quatek, USA) was used to test the surface potential of the polylactic acid nanofiber filter membrane sample. The test height was 2 cm, and the temperature and humidity were constant at 25°C and 45%. 20 data points were randomly collected for each sample and the average value was taken.

[0107] Filtration performance test, air resistance test: LZC-K automatic filter material tester (Suzhou Huada Instrument Equipment Co., Ltd.) was used to test the polylactic acid nanofiber filter membrane sample (area 113.04cm 2), the gas flow rate is set to 85L / min, and the particle size range of the NaCl atomized particles produced by the aerosol generator is 0.1 to 10μm. At least 3 different positions are tested for each group of samples, and the results are averaged. The polylactic acid nanofiber filter membrane samples obtained in the above embodiments and comparative examples are placed in a LZC-K automatic filter material tester to test the filtration performance and air resistance of the samples. The side close to the aerosol generator is the upstream, and the side away from it is the downstream. The filtration efficiency is calculated by testing the PM concentration upstream and the PM concentration downstream. A differential pressure gauge is used to test the upstream pressure and the downstream pressure, and the air resistance (Pa) is obtained by calculating the difference between the two. At the same time, the surface potential of the polylactic acid nanofiber filter membrane samples was tested after standing for 7 days and 30 days respectively.

[0108] Filtration efficiency = (upstream PM concentration - downstream PM concentration) / upstream PM concentration × 100%.

[0109] Air resistance = the difference between upstream pressure and downstream pressure.

[0110] Table 1

[0111]

[0112] Test Example 2

[0113] The content of tetragonal barium titanate in the polylactic acid nanofiber filter membrane was tested using a thermogravimetric analyzer. First, a certain amount of the polylactic acid nanofiber filter membrane was taken and recorded as the initial mass, and the temperature was raised in a nitrogen environment at a heating rate of 10°C / min to 800°C, and the residual mass was measured.

[0114] Mass content of tetragonal barium titanate = residual mass / initial polylactic acid nanofiber filtration membrane sample mass × 100%

[0115] The mass content of tetragonal barium titanate in the polylactic acid nanofiber filtration membrane samples provided in Example 1, Comparative Example 1, Example 2 and Comparative Example 2 was tested, and the results are shown in Table 2.

[0116] Table 2

[0117] Content of Tetragonal Barium Titanate (wt%) Example 1 33.1 Comparative Example 1 0.02 Example 2 16.3 Comparative Example 2 10.0

[0118] It can be seen from the experimental data of Examples 1-5 and Comparative Examples 1-2 that the polylactic acid nanofiber filter membrane obtained by coaxial electrospinning of polylactic acid spinning solution and tetragonal barium titanate dispersion has high filtration efficiency, high surface potential and low air resistance, and maintains a high surface potential even after a long time (such as 7 days, 30 days). When the preparation method of the polylactic acid nanofiber filter membrane is changed, the filtration efficiency and surface potential of the prepared polylactic acid nanofiber filter membrane are significantly reduced, and the air resistance is significantly increased.

[0119] It can be seen from the experimental data of Examples 1-5 and Comparative Examples 3-6 that when the mass ratio of tetragonal barium titanate in the tetragonal barium titanate dispersion to polylactic acid in the polylactic acid spinning solution is 1: (1-10), the polylactic acid nanofiber filter membrane has a higher filtration efficiency, a higher surface potential and a lower air resistance, and maintains a higher surface potential even after a long time (such as 7 days, 30 days). When the mass ratio of the two is changed or any component is missing, or the barium titanate crystal phase is changed, the filtration efficiency and surface potential of the polylactic acid nanofiber filter membrane are significantly reduced, and the air resistance is significantly increased.

[0120] It can be seen from the experimental data of Examples 1-5 and Examples 6-7 that when the mass concentration of tetragonal barium titanate in the tetragonal barium titanate dispersion is 10-30wt%, the obtained polylactic acid nanofiber filter membrane has excellent performance, which is manifested as having high filtration efficiency, high surface potential and low air resistance. When the mass concentration of tetragonal barium titanate changes, the dispersibility of tetragonal barium titanate is reduced, resulting in poor performance of the polylactic acid nanofiber filter membrane, that is, the filtration efficiency and surface potential are significantly reduced, and the air resistance is significantly increased.

[0121] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0122] The present application is to electrospin polylactic acid spinning solution and tetragonal barium titanate dispersion solution coaxially, that is, in the process of electrospinning the polylactic acid static spinning solution to obtain polylactic acid fiber, the tetragonal barium titanate dispersion solution is electrostatically sprayed onto the surface of the polylactic acid fiber. The preparation method utilizes the high dielectric constant and excellent piezoelectricity of tetragonal barium titanate (BTO), independently controls the amount of polylactic acid spinning solution and tetragonal barium titanate dispersion solution through coaxial electrospinning, and promotes the uniform dispersion of tetragonal barium titanate on the fiber surface, so that the tetragonal barium titanate and polylactic acid produce a synergistic effect, thereby preparing a polylactic acid nanofiber filter membrane with high surface potential, high filtration efficiency and low air resistance.

[0123] In addition, the polylactic acid nanofiber filter membrane can maintain a high surface potential even under long-term action, not only has excellent filtering performance, but also can generate piezoelectric charge through normal human breathing or wind vibration. In addition, it also has good biocompatibility and degradability, can achieve sustainable development of the environment, and is an air filtration material with broad application prospects.

[0124] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a polylactic acid nanofiber filter membrane, characterized in that: The steps include: Providing a tetragonal barium titanate dispersion and a polylactic acid spinning solution, coaxially electrospinning the polylactic acid spinning solution and the tetragonal barium titanate dispersion, and obtaining a polylactic acid nanofiber filtration membrane after drying; Wherein, the mass ratio of the tetragonal barium titanate in the tetragonal barium titanate dispersion to the polylactic acid in the polylactic acid spinning solution is 1:(1-10).

2. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 1, characterized in that: The mass concentration of the tetragonal barium titanate in the tetragonal barium titanate dispersion is 10 to 30 wt %; And / or, the mass concentration of the polylactic acid in the polylactic acid spinning solution is 5 to 25 wt %.

3. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 1, characterized in that: The operating parameters of the coaxial electrospinning are: the spinning voltage of the tetragonal barium titanate dispersion is 20 to 50 kV, and the consumption rate of the tetragonal barium titanate dispersion is 0.1 to 50 mL / h; the spinning voltage of the polylactic acid spinning solution is 20 to 50 kV, and the consumption rate of the polylactic acid spinning solution is 0.1 to 50 mL / h; the temperature is 10 to 30°C, the receiving distance is 10 to 30 cm, and the drum speed is 100 to 4000 rpm.

4. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 1, characterized in that: The solvent of the tetragonal barium titanate dispersion is a first organic solvent, and the first organic solvent includes at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform.

5. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 1, characterized in that: The tetragonal barium titanate dispersion also includes a dispersant; Preferably, the mass ratio of the dispersant to the tetragonal barium titanate is 1:100 to 1:1000; Preferably, the dispersant includes at least one of alkyl glycoside, polyvinyl pyrrolidone, ammonium polymethacrylate, sodium hexametaphosphate, dodecyldimethylaminoethyl lactone, and hexadecyltrimethylammonium bromide.

6. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 1, characterized in that: The solvent of the polylactic acid spinning solution is a second organic solvent; the second organic solvent includes at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane and chloroform.

7. The method for preparing a polylactic acid nanofiber filtration membrane according to any one of claims 1 to 6, characterized in that: The preparation method of the tetragonal barium titanate in the tetragonal barium titanate dispersion comprises the following steps: mixing a barium source, an acid solution, a titanium source and an alcohol to obtain a barium titanate gel; and then calcining the barium titanate gel to obtain the tetragonal barium titanate; Preferably, the mass ratio of the barium source to the acid solution is (0.1-10):(99.9-90); Preferably, the mass ratio of the titanium source to the alcohol is (0.1-10): (99.9-90); Preferably, the molar ratio of the barium element in the barium source to the titanium element in the titanium source is 1:10 to 10:

1.

8. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 7, characterized in that: The barium source includes at least one of barium sulfate, barium nitrate, barium acetate, barium hydroxide, barium chloride, and barium carbonate; And / or, the acid solution includes at least one of acetic acid, hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid; And / or, the titanium source includes at least one of tetrabutyl titanate, isopropyl titanate, and tetraethyl titanate; and / or, the alcohol comprises at least one of methanol, ethanol, n-propanol, isopropanol, and isobutanol; And / or, the calcination temperature is 500-1200° C., and the calcination time is 0.5-6 hours.

9. A polylactic acid nanofiber filtration membrane obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the polylactic acid nanofiber filter membrane according to claim 9 in air filter materials.

Citation Information

Patent Citations

  • Air filtering membrane based on nano-hybrid modified polylactic acid fiber and preparation method of air filtering membrane

    CN115961428A

  • Polylactic acid / citral electrostatic spinning nanofiber membrane as well as preparation method and application thereof

    CN116377653A

  • Preparation method of molybdenum sulfide coated barium titanate nanofiber

    CN116590809A

  • Nanofiber filtering membrane and preparation method and application thereof

    CN117225204A

  • Technology for preparing high-purity nano barium titanate powder

    CN1472141A